Effect of an educational intervention on breastfeeding knowledge and attitude among interns at Cairo University Hospital - Ola A. Mostafa; Marwa R. Salem; Ahmed M. Badr (Journal of the Egyptian Public Health Association, 2019)
Abstract Background Professional advice provided to mothers has an effective role on the prevalence and duration of breastfeeding. Previous studies showed that health care providers had defective knowledge and skills necessary to promote and support breastfeeding. Aim To assess breastfeeding-related knowledge and attitude among interns at Cairo University Hospital, before and after the provision of breastfeeding educational training sessions. Materials and methods The first phase was a cross-sectional study, conducted in Cairo University Hospital (Kasr Al Ainy) among 137 interns. The second phase was a pre-post interventional design. A pretested self-administered questionnaire was used to explore breastfeeding-related knowledge and attitude before, immediately after, and 3 months after breastfeeding educational sessions. Results Participants’ mean age was 23.7 ± 0.81, (range 22–27 years), with equally distributed males and females. The median total knowledge percent score was 56.4 (45.2–64.5). The highest median subtotal knowledge percent score was for effective feeding 100 (100–100), and the least median was for breast milk expression 20 (0:40). Participants’ knowledge improved after the educational intervention: The subtotal knowledge scores showed a statistically significant improvement immediately after and 3 months after the intervention in the following items: advantages for the baby, colostrum, duration, complementary feeding, and breast milk expression. The median total attitude percent score was 80 (74.1–83.5) and significantly improved immediately after the intervention. Conclusion Baseline knowledge and attitude scores among interns significantly improved after the intervention. Therefore, adoption of different curricular and extracurricular activities to improve breastfeeding knowledge and skills is required.